Efectividad del uso del láser en desinfección de conductos radiculares. - Lescano Alvarado, Jessenia Belen (2024)
The present research work is about “THE DISINFECTION OF ROOT CANALS STANDS BY THE BIOMECHANICAL PREPARATION WITH THE USE OF IRRIGATING SOLUTIONS AND THE APPLICATION OF ACTIVATING METHODS. Because of the presence of persistent microorganisms and the complexity of the root anatomy, new technologies have been implemented to improve cleaning. The aim of this research work is to analyze the effectiveness of lasers in disinfection of root canals, identify the types of lasers used in disinfection, determine the antimicrobial scope, and establish the disinfection techniques used with irradiation, based on a bibliographic review supported by scientific sources indexed in databases such as Pubmed, Scielo, Science Direct, Lilacs, and Google Scholar. The articles analyzed were from the academic period 2013 , of which 14 were chosen for this review process. As a result, lasers are used in the disinfection of canal having significant effects on bacterial reduction, showing a high capacity to penetrate deep and superficial dentin. The laser technology has been proposed in endodontics to improve the effectiveness of irrigation solutions and removal of smear layer.